Exploring Primary Care Physicians’ Experiences of Language and Cultural Discordant Care for Linguistic Minority Patients at the End-of-Life: A Study Protocol - Lee, Seung Heyck; Gibb, Maya; Karunananthan, Sathya; Cody, Margaret; Tanuseputro, Peter; Johnston, Sharon; Kendall, Claire; Bedard, Daniel; Collin, Stéphanie; Kehoe MacLeod, Krystal (International Journal of Qualitative Methods, 2023)
Health disparities exist across different linguistic groups. Language barriers in primary care can negatively affect access to healthcare services and the quality and safety of care at the end-of-life. This study will take a novel, in-depth look at the experience of language- and/or cultural-discordant care for adults from linguistic minority groups through the eyes of primary care physicians providing palliative and/or end-of-life care. Language and cultural discordance means that the physician and patient do not speak the same language or are not from the same cultural background. Qualitative data from primary care physicians (n = 12–24) providing language-discordant end-of-life care to Francophone and/or Allophone older adults across different care models and diverse geographies in Ontario will be collected through semi-structured interviews. Reflexive thematic analysis will be used to report themes within the data and consider the influence of the social locations of the researcher and research participants, geographic considerations impacting service provision, and barriers imposed by differing primary care funding structures on the provision of palliative and end-of-life care for linguistic and cultural minority groups in Ontario. Findings from this study will identify the interconnections among language and cultural discordance, care model, geographic region, and physician perceptions of their combined effects on access to, and quality of, palliative and end-of-life care. This evidence will be key to informing clinical practice guidelines and mobilizing change to improve primary care access and quality for adults at the end-of-life from linguistic and cultural minority populations across Ontario. Keywords: language discordance, qualitative research, reflexive thematic analysis, palliative care, primary care physicians, semi-structured interviews

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.